Crop residues integration with nitrogen rates reduces yield-scaled nitrous oxide emissions and improves maize yield and soil quality - M.S. Rahman; J. Ferdous; N.J. Mumu; M. Kamruzzaman; C. Eckhardt; M. Zaman; C. Müller; M.M.R. Jahangir (Journal of Integrative Environmental Sciences)
Maize production requires a large amount of nitrogen (N). However, a greater part of the N used gets lost to the environment as reactive forms including nitrous oxide (N2O). N2O emissions and associated soil-related factors were measured in a maize (Zea mays L.) field in the 5th crop after initiation of the experiment in an annual maize-rice sequence. The treatments comprised two levels of crop residues (no residue, NR vs. 30 cm residue, CR) with four levels of N fertilizers (control; farmers’ practice, FP; national recommended dose, RD, and 125% of RD, 1.25 RD). Mean and cumulative N2O emissions increased with N rate coupled with either residue level. The CR coupled with 1.25 RD had 10% higher N2O emissions than the same rate as NR. In contrast, yield-scaled N2O emissions were equal in 1.25 RD coupled with either residue level. However, higher N2O emissions in CR than in NR can be offset by the corresponding improvement in soil elemental quality, e.g. soil organic carbon, total N, P, K and S. The N2O emission factor, ranged from 0.99 to 1.34, and was higher in CR coupled with 1.25 RD than in any other combination suggesting that optimization of N rate is one of the best options to reduce N2O emissions. Maize grain yield was higher in RD and 1.25 RD than in the farmers’ practice where the former two were similar to each other. Step-wise multiple regression showed that N application rate, soil organic carbon, total N and pH are the dominant factors controlling N2O emissions. Our results suggest that maize production can benefit from residue retention with the current N rate (RD) for better yield, soil quality and N2O mitigation.